Plant-derived extracts and metabolic modulation in leukemia: a promising approach to overcome treatment resistance - Arévalo, Cindy Mayerli; Cruz-Rodriguez, Nataly; Quijano, Sandra; Fiorentino, Susana (Frontiers in Molecular Biosciences, 2023)
Leukemic cells acquire complex and often multifactorial mechanisms of resistance to treatment, including various metabolic alterations. Although the use of metabolic modulators has been proposed for several decades, their use in clinical practice has not been established. Natural products, the so-called botanical drugs, are capable of regulating tumor metabolism, particularly in hematopoietic tumors, which could partly explain the biological activity attributed to them for a long time. This review addresses the most recent findings relating to metabolic reprogramming—Mainly in the glycolytic pathway and mitochondrial activity—Of leukemic cells and its role in the generation of resistance to conventional treatments, the modulation of the tumor microenvironment, and the evasion of immune response. In turn, it describes how the modulation of metabolism by plant-derived extracts can counteract resistance to chemotherapy in this tumor model and contribute to the activation of the antitumor immune system.